2007
DOI: 10.1001/archneur.64.7.974
|View full text |Cite|
|
Sign up to set email alerts
|

Stoichiometric Alteration of PMP22 Protein Determines the Phenotype of Hereditary Neuropathy With Liability to Pressure Palsies

Abstract: Background: Hereditary neuropathy with liability to pressure palsies (HNPP) is caused by a 1.4-megabase deletion at chromosome 17p11.2, which bears the PMP22 gene and other genes. However, whether other genes besides PMP22 contribute to the phenotype is unknown. Whether any mutation within the coding region of the PMP22 gene ultimately causes HNPP by reducing the amount of peripheral myelin protein 22 (PMP22) expressed in myelin is also unknown.Objective: To determine whether affected patients develop a phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 20 publications
3
30
0
1
Order By: Relevance
“…In HNPP this results in prolongation of the distal motor latencies and conduction slowing at typical sites susceptible to mechanical compression ( Fig. 4) (Gouider et al, 1995;Li et al, 2007). Our study demonstrated enlargement of nerves and fascicles restricted to sites of entrapment HNPP (Fig.…”
Section: How To Explain Our Sonographic Findings?supporting
confidence: 51%
See 1 more Smart Citation
“…In HNPP this results in prolongation of the distal motor latencies and conduction slowing at typical sites susceptible to mechanical compression ( Fig. 4) (Gouider et al, 1995;Li et al, 2007). Our study demonstrated enlargement of nerves and fascicles restricted to sites of entrapment HNPP (Fig.…”
Section: How To Explain Our Sonographic Findings?supporting
confidence: 51%
“…4) (Madrid and Bradley, 1975;Gouider et al, 1995;Gabreels-Festen and Wetering, 1999;Keller and Chance, 1999;Sander et al, 2000;Shy et al, 2002;Li et al, 2007Li et al, , 2013. In HNPP this results in prolongation of the distal motor latencies and conduction slowing at typical sites susceptible to mechanical compression ( Fig.…”
Section: How To Explain Our Sonographic Findings?mentioning
confidence: 99%
“…PMP22 encodes a tetra-span membrane protein primarily expressed in peripheral nerve myelin [68]. Mice with heterozygous knockout of Pmp22 recapitulate the pathology of humans with HNPP, including tomacula with excessive myelin decompaction that extends from paranodes to juxtaparanodes and internodes [9].…”
Section: Introductionmentioning
confidence: 99%
“…These include Leu4Ter,9 Leu7 fs,10, 11 Gly94 fs,12, 23 Tyr97 fs,24 and Thr99 fs25 PMP22 . Mutations that cause an HNPP phenotype eliminate the mutant allele by processes such as nonsense‐mediated decay 11, 26. Thus, these are complete loss‐of‐function alleles similar to traditional HNPP in which the PMP22 allele is deleted 13.…”
Section: Discussionmentioning
confidence: 99%
“…Most CMT1E mutations are missense mutations probably resulting in a gain‐of‐new protein function 8. In contrast, some PMP22 point mutations produce a loss‐of‐protein function by a shift in the protein reading frame, leading to premature termination of translation 9, 10, 11, 12. A similar loss of function can also be caused by the reciprocal deletion of PMP22 within 17p12 that caused the CMT1A duplication.…”
Section: Introductionmentioning
confidence: 99%